Flow Assurance Improvement by Injecting Pour Point Depressant Chemical through Permanent Coiled Tubing Gas Lift to Heavy Oil at MM-1 Well at MPA Field - harry budiharjo sulistyarso; nur suhascaryo; sebastianus riskadarto (Journal of Petroleum and Geothermal Technology, 2023)
The majority artificial lift used in MPA Field use PCTGL (Permanent coil tubing gas lift). PCTGL is installed on several monobore well or dual monobore well. Some wells in the MPA Field have waxy HPPO oil character with pour point between 85-100oF with API between 30-35. The well "MM-1" has a HPPO character with pour point 95oF. The character high Pour point oil of the well will be problem to be solved. The MM-1 well is produced with PCTGL. From the simulation, a PCTGL design was obtained at a depth of 2250 ft. With the character of HPPO oil, pour point depressant injection optimization is also carried out along with the injection of gas lift so that the chemical can work from the downhole. The results of the bottle test of pour point depressant use concentration of 1000 ppm to reach the target. The results of the field test showed that the concentration of Pour Point Depressant of 1026 ppm was able to change the pour point up to 65oF. The results of optimization production showed that the production of MM-1 wells was able to increase with production of 290 bopd.